THE ROLE OF INNOVATIVE PEDAGOGICAL TECHNOLOGIES IN THE TEACHING OF DRAWING (IN THE EXAMPLE OF THE 8TH CLASS) - Barotova Nilufar (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article provides scientific and practical information about the role of innovative pedagogical technologies in the teaching of drawing (in the case of the 8th grade).